Efficiency Of Production Factor Allocation Of Cattle Breeding Business (Case Study in Asto Mulyo Village, Punggur District, Central Lampung Regency) - Maimunah, Emi; Sirat, Muhiddin; Pratiwi, Detia Melati (JURNAL ILMIAH PETERNAKAN TERPADU, 2021)
The purpose of this study was to analyze some factors of beef cattle production in Asto Mulyo Village, Sub-district of Punggur, Central Lampung regency which has the positive effect on production, then carried out an analysis of the allocative efficiency of production factors, to determine the level of efficiency in terms of price factors used in the beef cattle business in Asto Mulyo Village. To test the significance of the factors of production, it is carried out using a regression test with the Cobb-Douglas function analysis. Meanwhile, the analysis of allocative efficiency can be analyzed by calculating the production function to find out Xi* or the number of optimum factors used. The results of the analysis of production factors indicate that the variables of the calf, feed, vaccine, and labor have a positive and significant effect on beef production. While for the results of the analysis of the allocative efficiency shows that the calf and feed variables are not cost-efficiency, so input should be reduced, vaccine variables are not yet cost-efficiency, therefore input must be added, and labor variables are almost cost-efficiency, hence there must still be a reduction on the input. Modern and technology-based livestock innovation is expected to be able to increase production and farmers’ income in Asto Mulyo Village, Punggur Sub-district, Central Lampung regency.